Brain-wide Mapping of Endogenous Serotonergic Transmission via Chemogenetic fMRI - Andrea Giorgi; Sara Migliarini; Alberto Galbusera; Giacomo Maddaloni; Maddalena Mereu; Giulia Margiani; Marta Gritti; Silvia Landi; Francesco Trovato; Sine Mandrup Bertozzi; Andrea Armirotti; Gian Michele Ratto; et al. (Cell Reports, 2017)
Summary: Serotonin-producing neurons profusely innervate brain regions via long-range projections. However, it remains unclear whether and how endogenous serotonergic transmission specifically influences regional or global functional activity. We combined designed receptors exclusively activated by designed drugs (DREADD)-based chemogenetics and functional magnetic resonance imaging (fMRI), an approach we term “chemo-fMRI,” to causally probe the brain-wide substrates modulated by endogenous serotonergic activity. We describe the generation of a conditional knockin mouse line that, crossed with serotonin-specific Cre-recombinase mice, allowed us to remotely stimulate serotonergic neurons during fMRI scans. We show that endogenous stimulation of serotonin-producing neurons does not affect global brain activity but results in region-specific activation of a set of primary target regions encompassing corticohippocampal and ventrostriatal areas. By contrast, pharmacological boosting of serotonin levels produced widespread fMRI deactivation, plausibly reflecting the mixed contribution of central and perivascular constrictive effects. Our results identify the primary functional targets of endogenous serotonergic stimulation and establish causation between activation of serotonergic neurons and regional fMRI signals. : Giorgi et al. combined chemogenetics and functional magnetic resonance imaging (chemo-fMRI) to establish causation between serotonin release and regional functional activity. They show that endogenous serotonergic transmission does not affect global brain activity but selectively activates a set of target regions that serve as primary effectors of this modulatory system. Keywords: DREADD, connectivity, clozapine, CNO, CBV, dopamine, citalopram, pharmacokinetics